The Influence of Work-Life Balance Policy, Work Culture, and Managerial Support on Employee Retention in Creative Industries in West Java - Komariyah, Imas; Pahrijal, Rival (Westscience Press, 2024)
This study investigates the effect of work-life balance policies, work culture, and managerial support on employee retention in creative industries in West Java through quantitative analysis. A sample of 150 employees from various sectors within the creative industry participated in the study. Data were collected using structured surveys measuring perceptions of work-life balance policies, work culture, managerial support, and employee retention intentions. Structural Equation Modeling with Partial Least Squares (SEM-PLS) was employed to analyze the relationships between the variables. The results indicate significant positive relationships between work-life balance policies, work culture, managerial support, and employee retention intentions. These findings underscore the importance of fostering a supportive and conducive work environment in promoting employee retention within the dynamic landscape of the creative industries. The study contributes to the existing literature by providing insights into effective strategies for enhancing employee retention in creative industries in West Java.